Introduction [in Global Nutrition Report 2015] - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Good nutrition signals the realization of people’s rights to food and health. It reflects a narrowing of the inequalities in our world. Without good nutrition, human beings cannot achieve their full potential. When nutrition status improves, it helps break the intergenerational cycle of poverty, generates broad-based economic growth, and leads to a host of positive consequences for individuals, families, communities, and countries. Good nutrition provides both a foundation for human development and the scaffolding needed to ensure it reaches its full potential. Good nutrition, in short, is an essential driver of sustainable development.